2019
DOI: 10.1186/s12879-019-4452-y
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairments in patients with persistent symptoms attributed to Lyme disease

Abstract: Background Persistent symptoms attributed to Lyme borreliosis often include self-reported cognitive impairment. However, it remains unclear whether these symptoms can be substantiated by objective cognitive testing. Methods For this observational study, cognitive performance was assessed in 280 adults with persistent symptoms attributed to Lyme borreliosis (as part of baseline data collected for the Dutch PLEASE study). Cognitive tes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Although some studies find self-reported cognitive problems in a considerable proportion of patients with treated neuroborreliosis [ 2 , 4 ], we were not able to find reduced cognitive function in our cohort. Our results are in line with Dersch et al [ 15 ] and Berende et al [ 14 ], but contrary to studies finding reduced verbal learning/memory and attention/executive function [ 10 , 11 , 38 40 ]. There are several possible explanations for the different results.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although some studies find self-reported cognitive problems in a considerable proportion of patients with treated neuroborreliosis [ 2 , 4 ], we were not able to find reduced cognitive function in our cohort. Our results are in line with Dersch et al [ 15 ] and Berende et al [ 14 ], but contrary to studies finding reduced verbal learning/memory and attention/executive function [ 10 , 11 , 38 40 ]. There are several possible explanations for the different results.…”
Section: Discussionsupporting
confidence: 92%
“…Since none of the controls were asked to grade subjective memory or concentration problems, and the clinical composite score is unvalidated, we do not know whether mild subjective concentration/ memory problems are frequent in the control group or the general population. A modest association between self-reported cognitive problems and results on neuropsychological test-results has been documented previously, both in patients with neuroborreliosis [ 14 ] and other patient groups [ 44 , 45 ]. We did not include a questionnaire to assess patients’ subjective cognitive problems in detail, nor did we ask them about their expectancy regarding the outcome when included in the acute phase.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In line with previous studies, this study indicates that self-reported symptoms are clinically relevant with regard to daily functioning. 34 We recommend that this definition of persistent symptoms is used in future studies into this topic, allowing for comparison of findings between studies. Lastly, the longitudinal assessment of symptoms enabled describing the course and severity of symptoms over time.…”
Section: Discussionmentioning
confidence: 99%
“…However, self-reported cognitive deficits do not always correlate with performance on neuropsychological tests. Berende et al found no association between self-reported cognitive difficulties in over two hundred LB patients and performance on objective tests of episodic memory, working memory / attention, verbal fluency, information-processing speed, and executive function ( 73 ). Less than 3% of participants had cognitive deficits based on neuropsychological testing, a rate comparable to the general population.…”
Section: Discussionmentioning
confidence: 99%